Imagens da memória do audiovisual publicitário brasileiro a partir das práticas dos youtubers - Vargas, Carlos Eduardo Saraiva (Universidade do Vale do Rio dos Sinos, 2024)
This dissertation explores the Brazilian audiovisual advertising memory present in the content creation practices of YouTubers. Throughout our investigation, we conducted an exploration on the YouTube platform, seeking to understand how Brazilian audiovisual advertising memory, initially produced for television, is showcased in the context of content production practices by YouTubers. To achieve this, we selected two channels as observable units that utilize the theme of audiovisual memory as their main content: Canal 90 and Arquivos 1000. Initially, we provided a contextualization of the trajectory of the YouTube platform since its inception, exploring its characteristics and its interactions with users, advertising, and contemporary technological culture. Building on this contextualization, we progressed towards the central issue, empirically analyzing our observables and establishing connections with modalities of audiovisual content storage. Along this path, we conducted online excavations, inspired by the perspective of media archaeology, to find elements that compose and characterize these audiovisual memory practices. During our investigation, we focused on the remediation of these contents, with emphasis on the practices of YouTubers. Pertinent reflections emerged regarding the presence and practices of these creators within the platform. Furthermore, we identified significant changes occurring in these practices over the analyzed period. In this process, we grounded our reflections in the contributions of authors such as Georges Didi-Huberman (2006), Gustavo Fischer (2012), Lev Manovich (2001), Jay David Bolter and Richard Grusin (1999), Walter Benjamin (2006), Henri Bergson (2006), and Crystal Abdin (2018). This theoretical contextualization allowed us to identify how some YouTubers, through their channels on the platform, strategically use audiovisual advertising memory, creating a variety of content with distinct approaches.
Keywords: Memória; Audiovisual publicitário; Imagem; YouTubers; Memory; Audiovisual advertising; Image; ACCNPQ::Ciências Sociais Aplicadas::Comunicação